Inkonsistensi Putusan MK No. 49/PUU-X/2012 dan Putusan MK No. 22/PUU-XVII/2019 Terkait Peraturan Jabatan Notaris - Mahendrawati H.P., Yunita (Acta Comitas : Jurnal Hukum Kenotariatan, 2019)
Decision of the Constitutional Court No. 49 / PUU-X / 2012 which cancels the phrase "with the approval of the MPD" resulting in the authority of the MPD stipulated in Article 66 paragraph (1) of Law No. 30 of 2004 concerning the Position of Notary (UUJN) resulting in the loss of MPD's authority to give approval to investigators, prosecutors or judges for judicial proceedings involving notary public. Then the article was the subject of a lawsuit to be petitioned for material testing at the Constitutional Court, which was then terminated in Decision of the Constitutional Court No. 22 / PUU-XVII / 2019. However, the ruling of the Constitutional Court's ruling gave rise to a ruling that was different from the previous ruling, which stated that "Article 66 paragraph (1) UUJNP does not contradict the 1945 Constitution". The purpose of this paper is to find out changes to the regulations of the position of the Notary public after Decision of the Constitutional Court No. 49 / PUU-X / 2012 and to assess the inconsistency of the Constitutional Court's Decision on the review of material in Article 66 UUJN. This research is a normative legal research using the law approach, conceptual approach and case approach. The analyzed legal materials are primary and secondary legal materials with descriptive, comparative, evaluative and argumentative analysis techniques. Amendment to the regulation of the Notary Public after Decision of the Constitutional Court No. 49 / PUU-X / 2012 which abolished the MPD's authority in giving approval, has been replaced by MKN as stipulated in Article 66 paragraph (1) of the UUJNP. Inconsistencies that occur in Decision of the Constitutional Court No. 49 / PUU-X / 2012 and Decision of the Constitutional Court No. 22 / PUU-XVII / 2019 in the case of material testing of Article 66, due to differences in the Constitutional Court's considerations which resulted in differences in ruling on the previous Decree declared contrary to the 1945 Constitution whereas the most recent Decision was stated not to contradict the 1945 Constitution. The legal implications of the inconsistency have resulted in legal uncertainty and decreased public confidence in the judiciary . Putusan Mahkamah Konstitusi (MK) No. 49/PUU-X/2012 telah membatalkan frasa “dengan persetujuan Majelis Pengawas Daerah” Pada Pasal 66 ayat (1) Undang-Undang No. 30 Tahun 2004 tentang Jabatan Notaris (UUJN) mengakibatkan hilangnya kewenangan MPD yakni terkait pemberian persetujuan terkait proses peradilan oleh penyidik, penuntut umum, atau hakim. Namun dengan lahirnya Undang-Undang Nomor 2 Tahun 2014 tentang Perubahan Atas UUJN (UUJNP) kembali menghadirkan frasa yang pernah dibatalkan oleh putusan MK dengan nama badan yang berbeda yaitu “Majelis Kehormatan Notaris (MKN)” di pasal yang sama yang pernah dibatalkan oleh MK yakni Pasal 66 ayat (1). Kemudian pasal tersebut kembali menjadi pokok gugatan perkara untuk dimohonkan pengujian secara materiil di MK yang kemudian diputus dalam Putusan MK No. 22 /PUU-XVII/2019. Namun amar putusan MK ini memunculkan amar yang berbeda dengan putusan sebelumnya, yang menyatakan bahwa “Pasal 66 ayat (1) UUJNP tidak bertentangan dengan UUD 1945”. Adapun tujuan dari penulisan ini yakni untuk mengetahui perubahan peraturan jabatan Notaris pasca adanya Putusan MK No. 49/PUU-X/2012 dan untuk mengkaiji mengenai inkonsistensi Putusan MK terhadap pengujian materi pada Pasal 66 UUJN. Penelitian ini merupakan penelitian hukum normatif dengan menggunakan pendekatan undang-undang, pendekatan konseptual dan pendekatan kasus. Bahan hukum yang dianalisa berupa bahan hukum primer dan sekunder dengan teknik analisa deskriptif, komparatif, evaluative dan argumentatif. Perubahan pengaturan Notaris pasca Putusan MK No. 49/PUU-X/2012 yang menghapuskan kewenangan MPD dalam memberi persetujuan, telah digantikan oleh MKN yang tertuang dalam Pasal 66 ayat (1) UUJNP. Inkonsistensi yang terjadi dalam Putusan MK No. 49/PUU-X/2012 dan MK No. 22/PUU-XVII/2019 dalam hal pengujian materiil Pasal 66, disebabkan karena perbedaan pertimbangan MK yang mengakibatkan perbedaan amar pada Putusam sebelumnya dinyatakan bertentangan dengan UUD 1945 sedangkan pada Putusan terbaru dinyatakan tidak bertentangan dengan UUD 1945. Implikasi hukum akibat inkonsistensi tersebut mengakibatkan adanya ketidakpastian hukum dan menurunnya kepercayaan publik kepada peradilan.